2008
DOI: 10.1152/ajpcell.00367.2007
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide synthase signaling within cardiac myocytes targets phospholamban

Abstract: Studies have shown that neuronal nitric oxide synthase (nNOS, NOS1) knockout mice (NOS1-/-) have increased or decreased contractility, but consistently have found a slowed rate of intracellular Ca2+ ([Ca2+]i) decline and relengthening. Contraction and [Ca2+]i decline are determined by many factors, one of which is phospholamban (PLB). The purpose of this study is to determine the involvement of PLB in the NOS1-mediated effects. Force-frequency experiments were performed in trabeculae isolated from NOS1-/- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(112 citation statements)
references
References 44 publications
(75 reference statements)
12
95
0
5
Order By: Relevance
“…Although, unlike many gene deletion studies since, these authors did not find any difference in basal Ca 2ϩ transients and sarcomere shortening. Wang et al, 32 also found an increased response to ISO in eNOS Ϫ/Ϫ myocytes, although in this study a high concentration of 1 mmol/L ISO was used and the specific eNOS inhibitor L-N 5 -(1-iminoethyl)-ornithine had little effect on the ISO response of wild-type myocytes. In contrast, Martin et al, 33 describe enhancement of the contractile response to 100 nmol/L ISO in nNOS Ϫ/Ϫ and no significant difference in eNOS Ϫ/Ϫ mouse myocytes.…”
Section: Diurnal Variation In ␤-Adrenergic Stimulation Reflect Changementioning
confidence: 60%
“…Although, unlike many gene deletion studies since, these authors did not find any difference in basal Ca 2ϩ transients and sarcomere shortening. Wang et al, 32 also found an increased response to ISO in eNOS Ϫ/Ϫ myocytes, although in this study a high concentration of 1 mmol/L ISO was used and the specific eNOS inhibitor L-N 5 -(1-iminoethyl)-ornithine had little effect on the ISO response of wild-type myocytes. In contrast, Martin et al, 33 describe enhancement of the contractile response to 100 nmol/L ISO in nNOS Ϫ/Ϫ and no significant difference in eNOS Ϫ/Ϫ mouse myocytes.…”
Section: Diurnal Variation In ␤-Adrenergic Stimulation Reflect Changementioning
confidence: 60%
“…Increased NOS1 Activity on LV Contraction: Role of I Ca and SR Ca 2؉ Release NOS1 gene deletion has been reported to slow the rate of myocardial relaxation and SR Ca 2ϩ uptake 7,16 -18 and to have variable effects on I Ca , myocardial inotropy 14,15,17 and the diastolic leak of Ca 2ϩ through the RyR2. 23,24 In mGCH1-Tg mice, increased NOS1 activity did not affect LV systolic function (Online Figure II) or cardiomyocyte basal and ␤-adrenergic stimulated contraction ( Figure 4A and Online Figure III) Figure 4B) did not differ between genotypes, whereas the SR Ca 2ϩ content tended to be lower in mGCH1-Tg ( Figure 4C).…”
Section: Effect Of Myocardial Gch1 Overexpression Andmentioning
confidence: 99%
“…Myocardial overexpression of GCH1 hastens relaxation by increasing Ser 16 PLB phosphorylation. A, The PLB Ser 16 phosphorylated fraction (nϭ20 hearts per genotype) and the SERCA2A/total PLB ratio (nϭ4 hearts per genotype) were significantly increased in mGCH1-Tg mice (***PϽ0.0001 and *PϽ0.05 versus WT, respectively), whereas the PLB Thr 17 …”
Section: Transsarcolemmal Biopterins Transport and Myocardial Availabmentioning
confidence: 99%
See 1 more Smart Citation
“…4) (20,85). Our and others' work has shown that NOS1 is a key protein involved in these pathways (10,91,167,170). That is, in NOS1 knockout (NOS1 -/ -) mice, there is a blunted FFR and functional response to b-AR stimulation, which is similar to failing myocytes (i.e., decreased contractile reserve).…”
Section: Neuronal Nosmentioning
confidence: 97%